First Comparison of FLARIX Simulations with MSDP Observation of the C1.6 Solar Flare in the Hα Line of Hydrogen - Krzysztof Radziszewski; Petr Heinzel; Jana Kašparová; Michalina Litwicka; Arkadiusz Berlicki; Paweł Rudawy; Robert Falewicz (The Astrophysical Journal)
The primary objective of this study is to develop a time-dependent model of the flaring atmosphere based on observational data. Here, we present, for the first time, a comparison between numerical simulations of the flaring emission, specifically focusing on the hydrogen H α line, utilizing the FLARIX code and spectral observations of a compact C1.6 GOES-class flare observed on 2012 September 10, by the MSDP imaging spectrograph installed at the Białków Observatory. The Multichannel Subtractive Double Pass imaging spectrograph spectral data, collected with a temporal resolution as fine as 50 ms, enabled a comprehensive analysis of H α line profiles and light curves measured within an area of the flare’s emission. An initial atmospheric model close to VAL-C, with a modified temperature in the upper chromosphere, was employed in simulations. To enhance temporal resolution, modulations of the nonthermal electron (NTE) beam’s parameters were introduced based on variations in observed hard X-ray (HXR) flux (using RHESSI data). The synthesized H α line profiles were compared with the observed spectra. During the impulsive phase of the flare, the evolution of the observed and synthetic H α line intensity agrees, but discrepancies were found in intensities at specific wavelengths of the H α line profile. Fluctuations in the energy flux of NTEs exhibited a strong correlation with the H α emission during the HXR pulse. After considering various effects (such as the filling factor FF = 0.20) that could influence observed emissions, relatively good agreement between theoretical and observed lines was achieved.